Covid-19: Challenges in Long-Term Care Facilities for Older Adults in Hispanic American Countries - Patrick Alexander Wachholz; Alessandro Ferrari Jacinto; Ruth Caldeira de Melo; José Luis Dinamarca-Montecinos; Paulo José Fortes Villas Boas (Brazilian Society of Geriatrics and Gerontology, 2024)
INTRODUCTION: Little is known about management and mitigation of COVID-19 in long-term care facilities (LTCF) for older adults in Latin America. OBJECTIVE: To describe how the management of LTCF in Hispanic American countries plan and adapt their routines for coping with COVID-19 and whether they have been able to fulfill recommendations published by the World Health Organization (WHO). METHODOLOGY: A cross-sectional study was conducted by online survey of managers of LTCF located in Hispanic American countries. A 46-item questionnaire (adopting the WHO principles) was sent to participants. Descriptive statistics were used to summarize the data. RESULTS: Twenty-three care home managers replied, responsible for a total of 874 older people (range: 5 - 270). One questionnaire was excluded because of missing responses. Fourteen LTCF (63.60%) were private, for-profit facilities. The rate of compliance with WHO recommendations exceeded 70% for the majority of items. Just over half of the institutions had developed a strategic management plan, or had identified strategies for dealing with deaths of suspected cases. Difficulty acquiring personal protective equipment (PPE) was reported by 59.10% of the LTCF surveyed. The homes' capacity for SARS-Cov-2 testing was limited (36.36% of the institutions did not have any tests). CONCLUSIONS: The rate of compliance with recommendations published by the WHO for dealing with COVID-19 was greater than 70% at the majority of the LTCF surveyed. More than half of the institutions had strategic management plans. Availability of PPE and SARS-Cov-2 testing capacity were very unsatisfactory.